Muslims in Interwar Europe: A Transcultural Historical Perspective - Sajid, Mehdi; Ryad, Umar; Agai, Bekim (Muslim Minorities, 2015)
Muslims in Interwar Europe provides a comprehensive overview of the history of Muslims in interwar Europe. Based on personal and official archives, memoirs, press writings and correspondences, the contributors analyse the multiple aspects of the global Muslim religious, political and intellectual affiliations in interwar Europe. They argue that Muslims in interwar Europe were neither simply visitors nor colonial victims, but that they constituted a group of engaged actors in the European and international space. Contributors are Ali Al Tuma, Egdūnas Račius, Gerdien Jonker, Klaas Stutje, Naomi Davidson, Pieter Sjoerd van Koningsveld, Umar Ryad, Zaur Gasimov and Wiebke Bachmann.